Antropometri Pengguna dan Nilai Ergonomis Bangunan Bale Sakenem Pada Rumah Tinggal Tradisional Bali - I Wayan Parwata (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2019)
Traditional architecture is an architecture that is constructed based on or in accordance with the rules of the tradition adopted (Saliya, 2015). Traditional Balinese architecture is built following the layout, spatial layout and layout based on the concept of Asta Kosala Kosali and Asta Bumi (son, 1984). The architecture of traditional Balinese dwelling house is one of Indonesia's architectural works that need to be preserved and developed without eliminating the rules of local wisdom in Bali. In the setting of traditional Balinese homes in general has some period of building, among others: Holy place, Bale Meten (Bale Daje), Bale Dangin, Bale Dauh, Kitchen (Paon), and Jineng/Klumpu (place to store rice). The concept in traditional Balinese architecture is one of the concepts used in the technique of housing arrangement based on the anatomy of the Human Body (anthropometry) owner. The study uses the quasi experiment design. At this stage, modelling building